Agronomical characters of two populations of Jaltomata procumbens (Cav.) J. L. Gentry - Flores-Sánchez, I. Darío (2021)
Introduction. Jaltomata procumbens (Cav.) J. L. Gentry, used as food, is considered a semi-domesticated species (populations that have had a process of artificial selection but still have the ability to survive and reproduce without human intervention) and meets the criteria for future use. Objective. To evaluate agronomic traits of two J. procumbens populations, in greenhouse and hydroponics. Materials and methods. The research was carried out at the Colegio de Postgraduados, Campus Montecillo, Texcoco, State of Mexico, from July to December 2019. The following treatments were applied in an open hydroponic system: two populations (erect and decumbent), three electrical conductivity levels (CE): 1, 2, and 3 dS m-1 and two pruning levels (with and without pruning). The variables evaluated were: plant height (AP), stem diameter (DT), number of leaves (NH) and clusters (NR), flowers by clusters (FLR), fruits by clusters (FR), fruit weight (PF), yield (REND), and SPAD readings. Results. For both populations, their cultivation under greenhouse and hydroponic conditions promoted development in plant height, steam diameter, and fruit weight. Variability within and between populations was observed for pruning and electrical conductivity; the crop at 3 dS m-1 recorded the lowest plant height and the highest steam diameter, while at 1 dS m-1 the highest yield was obtained; for the pruning treatment, the highest values in flowers by cluster, fruit by cluster, and fruit weight were presented. Conclusion. Both populations showed the potential to be considered for studies in controlled environments.